2013
DOI: 10.1152/ajpgi.00064.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-specific deletion of hepatocyte nuclear factor-4α in adult mice results in increased hepatocyte proliferation

Abstract: Hepatocyte nuclear factor-4␣ (HNF4␣) is known as the master regulator of hepatocyte differentiation. Recent studies indicate that HNF4␣ may inhibit hepatocyte proliferation via mechanisms that have yet to be identified. Using a HNF4␣ knockdown mouse model based on delivery of inducible Cre recombinase via an adeno-associated virus 8 viral vector, we investigated the role of HNF4␣ in the regulation of hepatocyte proliferation. Hepatocyte-specific deletion of HNF4␣ resulted in increased hepatocyte proliferation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
115
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 38 publications
15
115
1
1
Order By: Relevance
“…In DGAT1-silenced cells, we examined the expression of hepatocyte nuclear factor 4␣ (HNF4␣) because this factor has been reported to be associated with CLDN1 expression in mice (32)(33)(34). In fact, HNF4␣ expression was markedly reduced in DGAT1-silenced cell lines at both the mRNA and protein levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In DGAT1-silenced cells, we examined the expression of hepatocyte nuclear factor 4␣ (HNF4␣) because this factor has been reported to be associated with CLDN1 expression in mice (32)(33)(34). In fact, HNF4␣ expression was markedly reduced in DGAT1-silenced cell lines at both the mRNA and protein levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HNF4␣ is a central regulator of hepatocyte differentiation and function (33,34) and is a major transcription factor that regulates the expression of genes that are involved in lipid homeostasis (42). HNF4␣ is also known to regulate the expression of proteins that are required for hepatic and intestinal tight junction assembly, including CLDN1, in mice (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, he is focusing on potential interactions between the Wnt/β-catenin pathway and hepatocyte nuclear factor 4 alpha (HNF4α), molecules that are involved in the development of the liver as well as CCA (35)(36)(37)(38)(39)(40). Studies in the laboratory have shown that knockdown of HNF4α in the zebrafish leads to a reduction in hepatocyte differentiation while genetic or chemical increase in β-catenin results in a loss of HNF4α and a maintenance of cholangiocyte differentiation.…”
Section: Ccf Grant Recipient Talksmentioning
confidence: 99%
“…P1-HNF4␣ acts as a tumor suppressor in the liver (24), inhibiting hepatocyte proliferation and inflammation (25)(26)(27). Several key players in proliferation, including p53, c-Myc, T-cell factor 4 (TCF4 [TCF7L2]), lymphoid enhancer factor 1 (LEF1 [LEF1]), and cyclin D1, have all been shown to physically interact with and antagonize P1-HNF4␣ (12,(28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%